Hitchcock and adaptation : on the page and screen - Osteen, Mark (Rowman and Littlefield, 2014)
This collection of essays examines the various Hitchcock films that were adapted from other sources (short stories, play, and novels). Some of these essays focus on the director's collaboration with such notable writers as John Steinbeck (Lifeboat), Thornton Wilder (Shadow of a Doubt), and Raymond Chandler (Strangers on a Train), proving not only that Hitchcock knew good writing when he read it, but that he was quite eager to exploit the cultural capital that these writers represented. Other essays discuss to what extent he was faithful (or not) to the source materials, his relationship with s.